Synthesis, biological activities and docking studies of pleuromutilin derivatives with piperazinyl urea linkage - Yuanyuan Zhang; Chuan Xie; Yang Liu; Feng Shang; Rushiya Shao; Jing Yu; Chunxia Wu; Xinghui Yao; Dongfang Liu; Zhouyu Wang (Taylor & Francis Group, 2021)
Antibiotics resistance is becoming increasingly common, involving almost all antibiotics on the market. Diseases caused by drug resistant bacteria, such as MRSA, have high mortality and negatively affect public health. The development of new drugs would be an effective means of solving this problem. Modifications based on bioactive natural products could greatly shorten drug development time and improve success rate. Pleuromutilin, a natural product from the basidiomycete bacterial species, is a promising antibiotic candidate. In this study, a series of novel pleuromutilin derivatives possessing piperazinyl urea linkage were efficiently synthesised, and their antibacterial activities and bactericidal properties were evaluated via MIC, MBC and Time-kill kinetics assays. The results showed that all compounds exhibited potent activities against tested strains, especially MRSA strains with MIC values as low as 0.125 μg/mL; 8 times lower than that of marketed antibiotic Tiamulin. Docking studies indicate substituted piperazinyl urea derivatives could provide hydrogen bonds and initiate π-π stacking between molecules and surrounding residues.